Pengaruh Budaya Organisasi dan Komitmen Kerja Terhadap Kepuasan Kerja Karyawan - Nur Kholis Huda; Andi Nu Graha; Sri Wilujeng (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2018)
This study aims to determine 1) the influence of organizational culture on employee job satisfaction, 2) the effect of work commitment on employee job satisfaction, 3) the influence of organizational culture and work commitment on employee job satisfaction. This research at PT. AXA Financial Indonesia Malang branch. The population in this study were all employees, amounting to 40, the sampling technique was by sampling saturation (total sampling). Data collection by distributing questionnaires and interviews and measurement of statement scores using the Likert scale 1-5. The analysis technique used is multiple linear regression. The results of this study indicate that organizational culture variables have a positive and significant effect on job satisfaction, work commitment variables have a positive and significant effect on job satisfaction as evidenced from the results of the t test. And organizational culture and work commitment have a positive and significant effect on job satisfaction as evidenced by the results of the F test.